Roles of Financial Literacy and Digital Financial Literacy in Enhancing MSME Financial Well-Being - Dian Saraswati, Birgitta; Daud Kameo, Daniel; Fevriera, Sotya; Huruta, Andrian; Andra Martian, Thomas (The European Journal of Applied Economics, 2026)
This study aims to examine the impact of financial literacy and digital financial literacy on the financial well-being of micro and small enterprise (MSE) owners. Primary data was obtained from surveys of MSE owners in Bantul Regency, Special Region of Yogyakarta Province. This research generated a sample through various sampling selection techniques (cluster, purposive, and accidental sampling). A total of 168 respondents were used for data analysis employing Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS software. Our results indicate that financial knowledge influences financial behaviors and attitudes, while digital financial knowledge affects digital financial behaviors and digital financial attitudes, and digital financial attitudes, in turn, impact digital financial behaviors. Furthermore, this study also documents that the financial behaviors, digital financial knowledge, and digital financial behavior dimensions affect financial well-being.  Micro and small enterprises will arguably make sound judgments, manage financial matters more effectively, and develop sustainable businesses if they have a better understanding of financial management and digital technology.